The Effect of Transformational Leadership of Madrasah Principals and Teacher Performance on Madrasah Quality - Rina Oktafia; Adripen Adripen; Lita Sari Muchlis (Tarbawi : Jurnal Ilmu Pendidikan, 2021)
This study aims to determine the effect of transformational leadership of madrasah principals and teacher performance on the quality of madrasah. The methodology used in this study is a descriptive method with a quantitative approach. The sample on this research is 70 teachers of State Islamic Senior High School (MAN) at Solok, West Sumatera, Indonesia. Data were collected using a Likert scale model questionnaire via a google form. Prerequisite tests performed were normality test, linearity test, homogeneity test, multicollinearity test, and heteroscedasticity test with SPSS application. The results of the prerequisite test state that all data are normally distributed, two independent variables have a linear relationship, the respondents from a homogeneous sample, there are no symptoms of multicollinearity, and two independent variables do not occur heteroscedasticity. Data were analyzed using simple regression, multiple regression, and partial correlation analysis. The results showed that the influence of transformational leadership of the madrasah principal on the quality was 0.846 (strong correlation), with an effect of 71.6%. In addition, the influence of teacher performance on the quality of madrasah was 0.740 (strong correlation), the effect is 54.8%. Furthermore, the influence of transformational leadership of madrasah principals and teacher performance on the quality of madrasah was 0.861 (strong correlation), while the effect is 73.3%, and other factors influenced the remaining 26.7%.